CCOMPLISHMENT OF ADOLESCENT DEVELOPMENTAL TASKS OF TENTH GRADE STUDENT OF PUBLIC SENIOR HIGH SCHOOL 3 AT TANJUNG RAJA - HARLINA, HARLINA; PUTRI, MELISA KARLYN (Sriwijaya University Learning and Education International Conference, 2016)
Developmental tasks were the tasks that have to be fullfilled during periods of individual lifetime. It would bring happiness if these tasks accomplished successfully. If individual was failed to accomplish these tasks, he or she might be having troubles through his/her life and being neglected. Fifty nine of tenth grade students were chosen as subject by systematic random sampling. Applying the Developmental Task Inventory (ITP) developed by Sunaryo Kartadinata et.al., the data showed that accomplishment of adolescent developmental task of the students was not optimal yet. At this period, students need to achieve individuality level but they have accomplished self-awareness and carefulness levels. This research findings could be considered by school counselors in developing guidance and counseling program for the students.